Original paperInsulin resistance and adiponectin levels in psoriasis patients - Janusz, Iwo; Lewandowski, Krzysztof; Lukamowicz, Jolanta; Świątkowska, Ewa; Narbutt, Joanna; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Psoriasis is an inflammatory skin disease affecting almost 2% of the population worldwide. Contemporary retrospective data obtained from patients with long-lasting psoriasis confirm increased incidence of cardiovascular diseases and metabolic disturbances and thus increased risk of sudden cardiac death in this group of patients. Aim : To evaluate insulin resistance and adiponectin levels as risk factors of cardiovascular disease development in psoriatic patients. Material and methods : Forty-two psoriasis vulgaris patients with negative history of cardiovascular diseases and polymetabolic disturbances were included in the study. Fasting blood glucose and adiponectin were measured and HOMA-IR (homeostasis model assessment of insulin resistance) was calculated. The obtained results were compared with the ones obtained from age and sex matched volunteers. Results : Increased insulin levels in psoriatic patients in comparison to the control group were observed. Also psoriatic patients presented increased HOMA-IR when compared with controls. Both the obtained results presented borderline values at statistical significance. There was no correlation between the above parameters and the disease duration. Also no statistically significant differences were noted in adiponectin levels in the examined groups. Conclusions : The observed clear tendency in fasting insulin levels and insulin resistance occurrence in psoriasis patients points to the influence of chronic inflammatory processes on carbohydrate metabolism in these patients. Key words: psoriasis, insulin resistance, adiponectin, polymetabolic syndrome.